2016
DOI: 10.31524/bkkmedj.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of size based pulmonary nodules in Asia.

Abstract: Recent advances on CT scan imaging followed by further investigation techniques (if applicable) such as endobronchial ultrasound (EBUS), fiberoptic bronchoscopy (FOB), video assisted thoracoscopy (VATS), surgery and pathological diagnosis have played a key role in the early and accurate diagnosis Abstract OBJECTIVE: To determine whether the American College of Chest Physicians' lung nodule screening recommendation is an effective tool in diagnosing Asian patients with pulmonary nodules. MATERIALS AND METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…One recent study from Thailand also observed a very high prevalence of TB in nodules # 8 mm but especially in smaller nodules (4.5-11 mm). 27 Compared with the CHEST guidelines, the expert panel suggested long-term CT surveillance (3 years and beyond) of small nodules in Asian individuals with a higher risk profile. Although the expert panel acknowledged that there are no data to explicitly support this approach, the recommendation is based on the natural history of slowly growing early-stage adenocarcinoma.…”
Section: 8mentioning
confidence: 99%
“…One recent study from Thailand also observed a very high prevalence of TB in nodules # 8 mm but especially in smaller nodules (4.5-11 mm). 27 Compared with the CHEST guidelines, the expert panel suggested long-term CT surveillance (3 years and beyond) of small nodules in Asian individuals with a higher risk profile. Although the expert panel acknowledged that there are no data to explicitly support this approach, the recommendation is based on the natural history of slowly growing early-stage adenocarcinoma.…”
Section: 8mentioning
confidence: 99%
“…We calculated the sample size based on the etiology of a size-based lung nodule in Asia by SawangSaenghirunvattana et al . " The prevalence (P) of the malignant nodule is 0.25 or 25% [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from the radiological picture archiving and communication system (PACS) database and the subject's case notes. We calculated the sample size based on the etiology of a size-based lung nodule in Asia by SawangSaenghirunvattana et al" The prevalence (P) of the malignant nodule is 0.25 or 25% [10].…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17] In our previous article, we reported nodules/ mass measuring 4.5-11 mm in our institution all caused by TB. 18 To further expound on the connection of lung nodule characteristics and diagnosis, we used the Mayo Clinic formula to find out if this is an effective and applicable tool in determining the probability of lung cancer in TB-endemic countries.…”
mentioning
confidence: 99%